Probing cavity versus surface preference of fluorescent template molecules in molecularly imprinted polystyrene microspheres - Sonawane, Swapnil L.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Functional polystyrene (PS) crosslinked microbeads were developed by dispersion polymerization as fluorescent molecularly imprinted polymers (MIPs) having cavities with specific recognition sites. The functional azobenzene molecule modified with pyridine was self-assembled with Pyrenebutyric acid (template molecules), and introduced during the second stage of dispersion polymerization of polystyrene. The template molecule was removed from MIP by Soxhlet using acetonitrile as solvent. Non imprinted polymer (NIP) having no template was also synthesized for comparative study. Fluorescence spectroscopy could be used as a tool to derive insight into the location of the template molecules on the MIP or NIP. The template molecules were adsorbed on the surface of the NIPs during binding studies, which was evidenced from the pyrene excimeric emission observed at 440 nm. The template binding efficiency of the NIPs were much lower compared to MIPs. Pyrene emission from MIP upon rebinding showed typical monomeric emission in the 375-395 nm range, confirming its location in isolated cavities. In rebinding studies of the template molecules, the MIPs selectively took up the template for which the cavity was designed, which demonstrated their selectivity towards template molecules. (C) 2017 Wiley Periodicals, Inc.